The endemic Hawaiian mealybug genus Phyllococcus Ehrhorn, 1916 (Hemiptera: Coccomorpha: Pseudococcidae): redescription of the type species and description of a new species on an endangered host plant, Cryptocarya mannii (Lauraceae) - Percy, Diana M.; Watson, Gillian W.; Hodgson, Chris J. (Zootaxa, 2024)
The endemic Hawaiian mealybug genus Phyllococcus Ehrhorn (Hemiptera: Coccomorpha: Pseudococcidae) was erected in 1916 as a monotypic genus for a gall-inducing mealybug collected on the island of Oahu on Urera sandwicensis (now referred to genus Touchardia) (Urticaceae) in 1911. The species induces deep horn-shaped galls on the leaves of the host plant. Here we redescribe the adult female and adult male of Ph. oahuensis (Ehrhorn) and designate a lectotype; and we report a new record for Ph. oahuensis from the island of Maui. Additionally, we describe the adult female and second- and third-instar female nymphs of a new gall-inducing Phyllococcus species, Ph. cryptocaryae Percy, Watson & Hodgson, sp. n., found in galls on the leaves of Cryptocarya mannii (Lauraceae) in the central Waianae Mountains on Oahu. Also found galling the same host plant, and often in close proximity on the same leaf, were immatures of the triozid psyllid, Paurotriozana adaptata Caldwell, 1940 (Hemiptera: Psylloidea: Triozidae). Both the new mealybug and the triozid psyllid appear to be geographically restricted to the only remaining tree of C. mannii on Oahu and are therefore extremely vulnerable to extinction.